The politics of electoral reform : changing the rules of democracy - Renwick, Alan , 1975- (Cambridge University Press, 2010)
"Elections lie at the heart of democracy, and this book seeks to understand how the rules governing those elections are chosen. Drawing on both broad comparisons and detailed case studies, it focuses upon the electoral rules that govern what sorts of preferences voters can express and how votes translate into seats in a legislature. Through detailed examination of electoral reform politics in four countries (France, Italy, Japan and New Zealand), Alan Renwick shows how major electoral system changes in established democracies occur through two contrasting types of reform process. Renwick rejects the simple view that electoral systems always straightforwardly reflect the interests of the politicians in power. Politicians' interests are complex; politicians are sometimes unable to pursue reforms they want; occasionally, they are forced to accept reforms they oppose. The Politics of Electoral Reform shows how voters and reform activists can have real power over electoral reform"